Penerapan Metode Profile Matching Dalam Sistem Pendukung Keputusan Pemilihan Teknisi Terbaik - Sawitri Sawitri; Nelly Astuti Hasibuan; Dito Putro Utomo (Building of Informatics, Technology and Science (BITS), 2022)
PT. Mitra Tunggal Perkasa is a distributor company engaged in the marketing of goods sales, the goods sold or marketed are heavy equipment types such as the Shark Komprssor machine. Maintenance on the compressor machine is usually carried out by a technician, in which case PT. Mitra Tunggal Perkasa selects the best technicians and also rewards technicians who will be the best alternative. The selection of the best compressor technician is done to help improve the technician's work power so that it becomes even better than the previous one. To assist the determination or selection in determining someone who deserves to be the best compressor engine technician, a decision support system is needed, and there are lots of criteria that every technician must have as a condition to become the best compressor engine technician. In this study, a case will be raised, namely looking for the best alternative based on predetermined criteria by applying the Profile Matching method. This method compares the actual data value of a profile to be assessed with the expected profile value, so that the difference in competence (GAP) can be seen. selected alternative, so that it can be used by each party in supporting the progress of the organization or company in achieving its goals through making the best decisions. The result of the Decision Support System for the Selection of the Best Mechanical Technician at PT. Mitra Tunggal Perkasa is alternative A2 with a value of 4,755 in the name of "Satish Kumar".